Telephone Service Interruption Weighting Adjustments for State Health Insurance Surveys - Michael Davern; James Lepkowski; Kathleen Thiede Call; Noreen Arnold; Tracy L. Johnson; Karen Goldsteen; April Todd-Malmlov; Lynn A. Blewett (SAGE Publishing, 2004)
Many states rely on telephone surveys to produce estimates of uninsurance. To the extent that people in households without telephones differ from those living in households with telephones, estimates will be biased due to lack of coverage of those in households without telephones. We find the disparity in estimates of uninsurance in the Current Population Survey (all people vs. those living in households without telephones) shows a similar association to the disparity found in the state surveys (all people vs. those living in households with telephone service interruptions). We adjust the state survey weights of those people living in households that experienced telephone interruptions to account for people living in households without telephones and evaluate whether the weighting adjustment for telephone service interruptions is advisable.